Study of the ψ(1S,2S) and ηc(1S,2S) Weak Decays into DM - Junfeng Sun; Yueling Yang; Jinshu Huang; Lili Chen; Qin Chang (Advances in High Energy Physics)
Inspired by the recent measurements on the J/ψ(1S)→Dsρ, DuK⁎ weak decays at BESIII and the potential prospects of charmonium at high-luminosity heavy-flavor experiments, we study ψ(1S,2S) and ηc(1S,2S) weak decays into final states including one charmed meson plus one light meson, considering QCD corrections to hadronic matrix elements with QCD factorization approach. It is found that the Cabibbo-favored ψ(1S,2S)→Ds-ρ+, Ds-π+, D¯u0K¯⁎0 decays have large branching ratios ≳10-10, which might be accessible at future experiments.